Economic Development and Environmental Degradation in Indonesia: Panel Data Analysis - Ilham, M Irsyad (Universitas Muhammadiyah Yogyakarta, 2021)
This study analyzed the relationship of economic development, population density, and the number of vehicles on environmental degradation from 31 provinces in Indonesia for the period 2011-2019. Panel data analysis, which is widely used to examine issues that could not be studied in either cross-section or time-series alone, is used herein. The empirical results support the hypothesis on the direction of causality from those three factors of environmental damage in the country. The results concluded that economic development, population density, and the number of vehicles impacted on environmental degradation in Indonesia. The smallest cross-section random effect indicates the lowest environmental quality when all factors are fixed. The empirical findings provide important policy implications for Indonesia and it will direct its economic development model towards a green economic one. On the other hand, the growth of the population should be equalized with growth in human development. The distribution of population should be equalized among provinces by opening a new economic cluster to supply new work-fields. In addition, it should be for the country to create a more-educated population in order to protect environmental quality. Despite the unstoppable growth of vehicles, the government should implement the development of eco-friendly combustion technology besides reducing fuel consumption. Moreover, the road-making by plastic-based material can be considered to prevent land damage from plastic waste and might also recycle plastics which has caused pollution in Indonesia.